2022
DOI: 10.1093/nar/gkac483
|View full text |Cite
|
Sign up to set email alerts
|

ARMC5 is part of an RPB1-specific ubiquitin ligase implicated in adrenal hyperplasia

Abstract: ARMC5 is implicated in several pathological conditions, but its function remains unknown. We have previously identified CUL3 and RPB1 (the largest subunit of RNA polymerase II (Pol II) as potential ARMC5-interacting proteins. Here, we show that ARMC5, CUL3 and RBX1 form an active E3 ligase complex specific for RPB1. ARMC5, CUL3, and RBX1 formed an active E3 specific for RPB1. Armc5 deletion caused a significant reduction in RPB1 ubiquitination and an increase in an accumulation of RPB1, and hence an enlarged P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 92 publications
(131 reference statements)
1
19
0
Order By: Relevance
“…We previously reported that ARMC5 was expressed predominantly in the cytosol [ 19 ]. However, we later found that if nuclear export was blocked, ARMC5 appeared in the nuclei of transfected HEK293 cells [ 45 ]. To determine the location of ARMC5 expression in neuronal cells, we transfected SK-N-SH neuronal cells with ARMC5-expressing constructs.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that ARMC5 was expressed predominantly in the cytosol [ 19 ]. However, we later found that if nuclear export was blocked, ARMC5 appeared in the nuclei of transfected HEK293 cells [ 45 ]. To determine the location of ARMC5 expression in neuronal cells, we transfected SK-N-SH neuronal cells with ARMC5-expressing constructs.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, it has been proposed that NEDD4 first mono-ubiquitylates RPB1 and then Elongin ABC -Cullin5 poly-ubiquitylates it, targeting RPB1 for proteasomal degradation [ 40 , 41 , 42 ]. Moreover, BRCA1/BARD1 and Cull3-based ARMC5 were also proposed to act as RPB1 E3 ligases [ 43 , 44 ], suggesting that several steps of ubiquitylation/de-ubiquitylation may be necessary for a timely-controlled RPB1 eviction from chromatin and degradation [ 26 ]. The fact that many E3 ligases have been implicated in RPB1 ubiquitylation might be either an indicator of a multistep process controlling RPB1 ubiquitylation and/or multiple mechanisms controlling RNAPII fate, with different E3 ligase complexes involved in different scenarios.…”
Section: Rnapii Ubiquitylationmentioning
confidence: 99%
“…Intracellular protein homeostasis is regulated by protein synthesis and degradation 1 . Proteins are degraded by two main proteolytic systems: the autophagy‐lysosome pathway and the ubiquitin‐proteasome system 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular protein homeostasis is regulated by protein synthesis and degradation. 1 Proteins are degraded by two main proteolytic systems: the autophagy‐lysosome pathway and the ubiquitin‐proteasome system. 2 Ubiquitination mediates the targeting of a substrate to the proteasome and the lysosome, a significant site for protein degradation.…”
Section: Introductionmentioning
confidence: 99%